(untitled) (BIS Humanities and Social Science, 2025)
Digital transformation in Indonesia’s financial system is increasingly driving the need for modern and secure payment instruments. Central Bank Digital Currency (CBDC), or Digital Rupiah, is an innovative solution developed by Bank Indonesia to face this challenge. However, the use of CBDC, which is based on an electronic system, has consequences for the protection of customers’ personal data. This research aims to analyze the relationship between financial innovation through CBDC and the protection of digital human rights, especially the right to customer privacy. The method used is a normative juridical approach by examining national regulations, including Law No. 27 of 2022 on Personal Data Protection and other related regulations. Comparative analysis is also conducted with international standards on data privacy, such as the European Union’s General Data Protection Regulation (GDPR). The results show that there is a dilemma between the need to monitor transactions to maintain monetary stability and prevent financial crime with the state’s obligation to protect citizens’ privacy rights. Therefore, a balanced regulatory framework is needed that guarantees transparency, cybersecurity, and the principle of data minimization in the implementation of CBDC, so that legal guarantees for the protection of personal data as part of digital human rights are guaranteed.